THE ROLE OF ARTIFICIAL INTELLIGENCE IN PRIMARY EDUCATION: SHAPING THE FUTURE OF THE ELEMENTARY CLASSROOM (International journal of artificial intelligence, 2026)
This article explores the transformative role of Artificial Intelligence (AI) in primary education, focusing on young learners aged 6 to 10. While traditional educational models often struggle with diverse learning paces, AI introduces hyper-personalized learning pathways through adaptive platforms that assess and respond to individual student needs in real-time. Furthermore, the integration of gamification and intelligent tutoring systems enhances cognitive engagement among children with short attention spans. The study highlights AI as an essential "co-pilot" for educators, automating administrative burdens and allowing teachers to focus on emotional mentorship. Additionally, the paper examines how AI revolutionizes inclusive education for neurodiverse and special needs students. While acknowledging the immense potential of technology, the article addresses critical risks, including data privacy concerns, the digital divide, and the potential erosion of social-emotional skills. Ultimately, it advocates for a hybrid "High-Tech and High-Touch" model, where AI serves as a powerful collaborative tool to enhance, rather than replace, human-centric teaching.